Effectiveness of home health education based on behaviour change theory in patients with hand-foot syndrome complicated by pain - Xia Cai; Jinfeng Li; Guanghui Li; Shimin Luo; Hongyu Meng; Jinhui Dai (Medicine, 2026)
Effect of home health education based on behavior change theory on hand, foot pain and quality of life in patients undergoing targeted immunotherapy for liver cancer. 70 liver cancer patients who developed hand and foot pain during targeted immunotherapy at the Third Affiliated Hospital of Sun Yat-sen University from April 2021 to June 2023 were selected as research subjects, and they were divided into a control group (35 cases) according to different admission times. Compared with the observation group (35 cases), the admission time was from April 2021 to July 2022 and August 2022 to May 2023 respectively. The control group implemented routine nursing intervention, and the observation group implemented pain home health education intervention based on behavior change theory. The pain (VAS), Self-rating Anxiety Scale (SAS) scores of the 2 groups of patients before and after the intervention were compared. Quality of life scale (HF-QoL) score. After nursing, the pain score of the observation group was lower than that of the control group ( P < .05); the anxiety score of the observation group was lower than that of the control group ( P < .05); the quality of life scores of the observation group were higher than those of the control group ( P < .05). Pain home health education based on behavior change theory can reduce the pain of patients with hand and foot pain during targeted immunotherapy for liver cancer, thereby improving anxiety and improving quality of life.